2022
DOI: 10.3389/fevo.2022.948640
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear genetic diversity and structure of Anastrepha ludens wild populations evidenced by microsatellite markers

Abstract: The Mexican fruit fly, Anastrepha ludens, is an important pest that causes widespread damage to a number of fruit crops in Mexico. The sterile insect technique (SIT) is commonly used for its control. However, the existence of natural barriers can give rise to a population structure in neutral loci and possibly behavioral or adaptive traits that interfere with SIT. For this reason, it is important to understand the genetic diversity and structure of A. ludens populations and to better understand the evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…All three samples also showed high levels of homozygosity, suggesting high levels of inbreeding. This may be unique to A. ludens because previous studies with wild populations reported that A. ludens showed high values of F-fixation [47][48][49], possibly reflecting limited dispersal of these populations and the tendency of this species to mate with related individuals, even in the field. Genetic drift may also be a relevant factor for the high levels of homozygosity since most of the samples used here were not in Hardy-Weinberg equilibrium.…”
Section: Discussionmentioning
confidence: 78%
“…All three samples also showed high levels of homozygosity, suggesting high levels of inbreeding. This may be unique to A. ludens because previous studies with wild populations reported that A. ludens showed high values of F-fixation [47][48][49], possibly reflecting limited dispersal of these populations and the tendency of this species to mate with related individuals, even in the field. Genetic drift may also be a relevant factor for the high levels of homozygosity since most of the samples used here were not in Hardy-Weinberg equilibrium.…”
Section: Discussionmentioning
confidence: 78%